Developing tactics for listening - Jack C. Richards (Oxford Univ. Press, 2003)
This title features: recordings that reflect everyday situations; follow-up listening and speaking activities; 'Over to You' sections for extra speaking practice; a student audio CD for practice outside the classroom; photocopiable speaking activities for each unit; and mid-term, final, and unit tests with audio CDs for easy student assessment.